Development Of Information Systems Orphanage (E-Orphanage) Web-Based - Zulhajji Zulhajji; Zurriyatun Thoyyibah; Suhartono Suhartono (Institut Bakti Nusantara, 2021)
This study aims to develop a Web-Based Orphanage Information System (e-Panti) at the Silaturrahmi Orphanage in Makassar City. The information system for the Orphanage (e-orphanage) is used as a tool in conveying information on the Silaturrahmi Orphanage in Makassar City to people who want to know the official information of the Silaturrahmi Orphanage and can make it easier for the public to donate online. This research belongs to the type of Research and Development (RD) research. The information system is designed using a prototyping development model. The research subjects in the development of this system are the caretaker of the orphanage, the orphanage and the community. The data analysis technique tested uses the ISO 25010 testing standard which includes aspects of Functionality Suitability, Performance Efficiency, Portability and Usability. Based on the results of the research, a Web-Based Orphanage Information System (e-orphanage) was obtained. In testing the Functionality Suitability aspect in the very feasible category, the Performance Efficiency aspect using the Gtmetrix class in the good category, the Portability aspect using the browserstack.com software, where the system is said to have fulfilled the portability aspect because this system can run well without errors and in good category, the aspect Usability in the very good category. So it can be concluded that the Web-Based Orphanage Information System (e-orphanage) is suitable for use at the Silaturrahmi Toddopuli Orphanage in Makassar City and is in accordance with the ISO 25010 feasibility standard.